Understanding the coarsening and degradation in a nanoscale nickel gadolinia-doped-ceria electrode for high-temperature applications. - Chen,J; Ouyang,M; Boldrin,P; Atkinson,A; Brandon,NP (ACS Applied Materials and Interfaces, 2020)
Nanostructure engineering is an effective approach to enhance the electrochemical performance of energy devices. While the high surface area of nanoparticles greatly enlarges the density of reaction sites, it often also leads to relatively rapid degradation as the particles tend to coarsen to reduce their high surface energy. Therefore, a nickel/gadolinia-doped-ceria (CGO) cermet electrode is studied, with a novel porous nanostructure consisting of nanoscale Ni (100 nm) and CGO (50 nm) crystallites, cosintered from nanocomposite precursor agglomerate particles. This electrode combines both high performance and excellent durability, with a total area-specific resistance (ASR) of 0.11 Ω cm2 at 800 °C and a stable ASR with up to 170 h ageing in humidified 5% H2-N2. Post-test analysis by 3D tomography shows that nickel coarsens and is responsible for the initial increase in ASR. However, the subsequent electrochemical performance is stable because reaction at the double phase boundaries (DPBs) on the surfaces of nanoscale CGO becomes dominant and is resistant to ageing. At this stage, the coarsened Ni network is also stabilized by the surrounding nanostructure. The dominant role of the DPB reaction is supported quantitatively using a continuum model with geometrical parameters obtained from 3D tomography.